2020
DOI: 10.1097/phh.0000000000001184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Training Gaps Among Public Health Practitioners in Washington State

Abstract: Identifying the training gaps in public health competencies and strategic skills is a first step in the development of effective workforce development plans and strategies. The purpose of this study was to identify training gaps in public health competencies and strategic skills among local, tribal, and State public health employees in Washington State using an online cross-sectional survey from 2016. Domains where participants reported to have low training confidence and high training needs were coded as "tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Participants noted the importance of public speaking skills and the need for communication skills training in the public health curriculums of university programs. Sainkhuu et al 12 found one‐quarter of public health practitioners identified they had training gaps in communication competencies. Importantly, public health professionals are keen to undertake further training to improve their skills in effective communication 13 …”
Section: Discussionmentioning
confidence: 99%
“…Participants noted the importance of public speaking skills and the need for communication skills training in the public health curriculums of university programs. Sainkhuu et al 12 found one‐quarter of public health practitioners identified they had training gaps in communication competencies. Importantly, public health professionals are keen to undertake further training to improve their skills in effective communication 13 …”
Section: Discussionmentioning
confidence: 99%
“…Measuring and assessing the effectiveness of training initiatives is crucial to ensure that the programs are yielding the desired outcomes (Sainkhuu et al, 2020;Hassan et al, 2024). This involves implementing robust evaluation mechanisms to gauge the impact of the training on the workforce.…”
Section: Designing and Implementing Training Programsmentioning
confidence: 99%
“… 1 6 Nevertheless, many public health professionals lack such competence. 6 8 For example in a national survey reported by Bogaert et al, 9 55%, 49%, and 31% of public health professionals, respectively, had competency gaps in financial management, systems/strategic thinking, and cultural competency. It appears, consequently, that skill enhancement for many public health workers is needed.…”
mentioning
confidence: 99%
“…Colleges and departments of public health, public health foundations, and expert practitioners have long agreed that competence in multiple core public health domains (analysis/assessment, leadership, cultural competency, etc) is desirable for public health professionals 1–6. Nevertheless, many public health professionals lack such competence 6–8. For example in a national survey reported by Bogaert et al,9 55%, 49%, and 31% of public health professionals, respectively, had competency gaps in financial management, systems/strategic thinking, and cultural competency.…”
mentioning
confidence: 99%